Planejamento e síntese de derivados cumarínicos com potencial leishamanicida e antitumoral - Rosa, Isael Aparecido (2014)
Coumarins are widely used in industry as synthetic intermediates of pesticides, drugs and pharmaceuticals. They are the subject of ongoing investigations of biological interest because of properties such as: anti-HIV, antituberculosis, anti-influenza, anti-Alzheimer disease, antiinflammatory, anti-microbial, immunosuppressive and anti-melanogenic. In this work the derivatives synthesis methylated, butylated, glycosylated and prenylated of coumarin were prepared, followed by characterization by spectroscopic and spectrometric techniques (IR, NMR and MS). Fourteen coumarin derivatives were synthesized from 7-hydroxy-4- phenylcoumarin (1), 7-dihydro-4-(4-chlorophenyl)coumarin (11) and 7-hydroxy-4-(4- fluorophenyl)coumarin (14) and have evaluated their activities against tumor cell lines, leishmanicide in promastigote and amastigote forms of Leishmaniaamazonensis strains and cytotoxicity in macrophages. In the anti-tumor activity test, the most significant results were for the 8 and 9 compounds. They were effective in inhibiting cell and capable of inducing apoptosis in A549 cell proliferation. This activity may be related to the ester substituent, once the starting structure showed not such activity. In leishmanicide test, only the derivatives showed significant activity against promastigotes, and compounds 3 and 7, about 2.5 times more activity than its precursor (1) and activity as effective as amphotericin B. The results suggest that the variation of the lipophilicity of the molecule is an important point for biological activity and that some structural changes made to coumarin derivatives led to more potent, selective and less toxic.